Atomistic and finite element study of nanoindentation in pure aluminum. (June 2020) - Mojumder, Satyajit; Mahboob, Monon; Motalab, Mohammad
Abstract: Nanoindentation is a useful technique to measure mechanical properties of a material such as the elastic modulus and hardness etc. In this paper, the effects of crystallographic orientation, indentation speed, indentation depth and indenter size has been studied for pure Aluminum (Al) using dislocation nucleation and propagation mechanism in atomistic simulation. The materials properties like hardness and reduced modulus are also calculated from the atomistic simulations. Nanoscale finite element (FE) simulations in Al are carried out using molecular dynamics tensile test data as input parameters and compared with atomistic results. The proposed methodology reduces the computational time and cost and reproduces the material properties with reasonable accuracy. The investigations of atomistic simulations include the load-displacement analysis, dislocation density and dislocation loops nucleation and propagation, von-Mises stress distribution and surface imprint. This study provides a pathway to obtain the materials properties for nanoscale materials without performing large scale atomistic simulation and can be applied for other mechanical properties such as fatigue, creep simulation of materials.